Economic analysis of small scale dairy buffalo enterprises in Bhola district of Bangladesh (Progressive Agriculture, 2017)
The purpose of this study was to analyze the socio-economic structure of water buffalo farming at some selected coastal areas of Bhola district of Bangladesh. Data were collected from the 35 small and large farms by surveying during the period January to March, 2015. The study revealed that buffalo rearing was mostly practiced by middle (30-45yrs) and old (>45yrs) aged farmers than young farmers (